ARCHEAN PROTOLITH AND ACCRETION OF CRUST IN KAMCHATKA: SHRIMP DATING OF ZIRCONS FROM SREDINNY AND GANAL MASSIFS - Bindeman I.N.; Vinogradov V.I.; Valley J.W.; Wooden J.L.; Natal'in B.A. (My University, 2002)
We used an ion microprobe (SHRIMP-RG) for U-Pb dating of individual zircons in high-grade metamorphic basements of the felsic Sredinny and mafic Ganal Massifs in Kamchatka. Thirty percent of zircons from paragneisses of the Sredinny Massif contain Archean (2800–2500 Ma), early Proterozoic (1700–2100 Ma), and late Proterozoic (∼1000 Ma) detrital cores. In addition, a broad and almost uninterrupted range of Phanerozoic detrital cores (460–175 Ma) is present, with Jurassic to Lower Cretaceous (150–96 Ma) zircons forming the youngest detrital age group. Ubiquitous -Ma rims signify the age of regional metamorphism, though yet another metamorphism is defined by four 77 2 47–53-Ma zircons. The abundance of Archean, Proterozoic, and Paleozoic zircon cores, as well as the short ∼20-m.yr. time lag between the youngest detrital zircon cores and the age of metamorphic rims, argues strongly against a long trans-Pacific transport and the origin of the Sredinny Massif as a piece of a continent other than Siberia. We suggest that the Sredinny Massif is an eastern part of the exposed basement (leading edge) of the Sea of Okhotsk (Okhotomorsk) microcontinent and that it represents a polymetamorphic accretionary wedge whose clastic sediments were derived from Siberia. Zircon ages from amphibolites and gabbro in the Ganal Massif exhibit two age groups, one at 60–80 Ma and the other at 18–40 Ma, and lack Precambrian cores. We interpret the Ganal Massif as the lower crust of an intraoceanic island arc. The Sredinny and Ganal Massifs, despite their present proximity, belong to different tectonic units and do not represent upper and lower crustal fragments of the same unit. We present a tectonic model that explains the origin of both Massifs as a part of Mesozoic and Cenozoic geodynamic history in the NW Pacific.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей